Justice environnementale et biopiraterie : le cas de l’Inde - Jérôme Ballet; Sylvie Ferrari (VertigO)
The aim of this article is to analyze how India has built its arsenal of defense against biopiracy since the ratification of the Nagoya Protocol in 2012. We want to emphasize and analyze the linkages between the activist movements in favor of environmental justice, their speeches and the arguments they use to tip the scales on their side, and the Indian state. This perspective is particularly interesting insofar as militant movements have largely influenced the country's legislative policy. Moreover, this influence was not achieved solely by the use of a fairly formatted discourse on environmental justice but also by the use of arguments linked to international legal frameworks. After studying the points of convergence and divergence between environmental justice and the protection of biodiversity in a global context, we analyze through case studies how this protection was built in India. Finally, the study of two relevant tools put in place by the Indian legislative system is proposed as a complementary track to strengthen the protection of biodiversity.